Case Report: Targeting the Achilles’ heel of monomorphic epitheliotropic intestinal T-cell lymphoma - Xue, Song; Gu, Hong-fei; Yang, Fan; Zhang, Wei; Liu, Xi-yang; Sun, Hui-peng; Cao, Xing-yu (Frontiers in Oncology, 2026)
BackgroundMonomorphic epitheliotropic intestinal T-cell lymphoma (MEITL) is a rare and highly aggressive lymphoma with a dismal prognosis and no established standard therapy. Its frequent expression of BCL-2 provides a rationale for targeting this anti-apoptotic protein.MethodsWe report the case of a 34-year-old female with refractory MEITL who failed prior lines of therapy, including CHOPE and gemcitabine/oxaliplatin (GemOx) combined with golidocitinib. Based on positive BCL-2 expression by immunohistochemistry, a salvage regimen combining venetoclax with Gemox was administered.ResultsThe treatment induced a rapid and significant clinical improvement. A follow-up PET/CT scan confirmed complete metabolic remission. The main adverse event was grade 4 neutropenia and thrombocytopenia with febrile neutropenia, attributable primarily to the Gemox backbone, which resolved with supportive care. The off-label use was approved by the institutional committee, and informed consent was obtained.ConclusionTo our knowledge, this is the first report of successful treatment of refractory MEITL with a venetoclax-containing regimen. This case validates BCL-2 as a actionable therapeutic target in MEITL. Future efforts should focus on optimizing combination partners for venetoclax to improve efficacy and tolerability. The rationale for exploring venetoclax as post-transplant maintenance therapy in MEITL is also discussed.